Harnessing the synergies of independent central banks and human capital for enhanced financial sector development in Africa - Abel Agoba; Ebenezer Bugri Anarfo; Yakubu Awudu Sare (Cogent Economics & Finance, 2022)
Using panel data from 2004 to 2012, we employ a two-step system GMM estimation technique, with robust standard errors, collapsed instruments and illus-trate marginal effects of central bank independence on financial development in Africa. We also examine the moderating roles of human capital, proxied by literacy rates on the CBI-financial development nexus. We find that, in countries with higher literacy rates/human capital, the positive impact of dejure CBI on financial development is enhanced. Higher literacy rates however, worsen the negative impact of de facto CBO on financial devel-opment. Independent central banks can be made more effective in achieving financial development through governments improving literacy rates. The study is the first to empirically examine the impact of central bank independence on financial development using both dejure and de facto CBI measures and literacy rates in explaining this relationship
Keywords: 330; Africa; Central Bank Independence; Developing Countries; Emerging Markets; Financial Development; Literacy Rates